Determination of Business Performance, Human Resources Competence, and Utilization of Accounting Information Technology on Financial Management in Aceh Province - Hendra Raza; Nazaina Nazaina; Khairisma Khairisma (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia are priorities in national economic development. This study aims to determine the effect of perception, level of education and socialisation as well as the driving factors for the application of financial accounting standards for micro, small and medium entities (determination of business performance, competence of human resources, and the use of accounting information technology on financial management of MSMEs in Aceh Province). MSMEs contributed the largest trade sector, as much as 46.17%, with a workforce distribution of 31.81%, which is one of the drivers of the people's economy and supports the Indonesian economy. In business, decision making must be rational and based on available information. It shows the importance of knowledge related to communication and capable human capable humans' decisions. This research design is descriptive and quantitative. This research was conducted on Micro, Small, and Medium Enterprises t is active in Aceh Province. Based on the study results, t can draw is that business performance has a significant effect on financial competence and has a substantial impact on the financial management of Micro, Small and Medium Enterprises. Accounting information technology has a considerable effect on the financial management of Micro, Small and Medium Enterprises.